Progressive Resistance Exercise and Parkinson's Disease: A Review of Potential Mechanisms - Fabian J. David; Miriam R. Rafferty; Julie A. Robichaud; Janey Prodoehl; Wendy M. Kohrt; David E. Vaillancourt; Daniel M. Corcos (Parkinson's Disease)
This paper reviews the therapeutically beneficial effects of progressive resistance exercise (PRE) on Parkinson's disease (PD). First, this paper discusses the rationale for PRE in PD. Within the first section, the review discusses the central mechanisms that underlie bradykinesia and muscle weakness, highlights findings related to the central changes that accompany PRE in healthy individuals, and extends these findings to individuals with PD. It then illustrates the hypothesized positive effects of PRE on nigro-striatal-thalamo-cortical activation and connectivity. Second, it reviews recent findings of the use of PRE in individuals with PD. Finally, knowledge gaps of using PRE on individuals with PD are discussed along with suggestions for future research.